Prevalence of alveolar bone crest resorption patterns at the age of 12-30 years from panoramic radiographs at RSGMP Universitas Trisakti - Billah, Arifah; Lubis, Muhammad Novo Perwira (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: The aim of this study is determine the prevalence of alveolar bone crest resorption patterns at the age of 12-30 years from panoramic radiographs. Materials and Methods: This study used consecutive sampling method based on secondary data from panoramic radiographs at the age 12-30 years, who had resorption on central insisivus and first molars at maxilla and mandibula. The samples used in this study were teeth 11, 21, 31, 41, 16, 26, 36 and 46 with using digital measurements from the CEJ to the top of the alveolar bone. Data is presented in tabular form with simple statistical calculations using SPSS and MS. Excel, and intraobserver reliability test. After the measurements were taken, intraobserver reliability was tested using the Cohen's Kappa test. Data processing was carried out using SPSS and Microsoft Excel. Results: The results of this study showed that the prevalence of patients diagnosed with periodontitis was 6.19% with Horizontal bone resorption 4,26% and vertical 1.93%. Conclusion: The prevalence of patients diagnosed with periodontitis in 2022 was 6.19% with horizontal bone destruction patterns of 4.26% and vertical 1.93%.